Community-Based Strategies in Islamic Religious Education (PAI): Fostering Youth Religious Character Formation through Majelis Taklim - Rumba Triana; Ali Maulida; Saqoikul Ilmi (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2025)
Adolescents today face serious challenges to their religious identity due to globalization, cultural shifts, and the influx of values that often contradict Islamic teachings. This study addresses the gap in research on non-formal Islamic education by examining how Majelis Taklim can contribute to fostering youth religious character. Using a qualitative case study approach, data were collected through observation, interviews, and documentation with adolescent participants, instructors, and community members at Majelis Taklim Miftahussalam in Kedung Jaya, Tanah Sareal, Bogor City. The findings reveal that learning strategies applied in this setting include interactive lectures and discussions, the wetonan method, practical demonstrations, provision of relevant materials, exemplary role modeling by ustadz, the integration of social media for da’wah, regular evaluations, and collaboration with families. These strategies have proven effective in strengthening adolescents’ religious character, as reflected in increased prayer discipline, Qur’an reading and memorization, respectful communication, and greater responsibility in learning, suggesting that community-based Islamic education can complement formal schooling in addressing contemporary challenges.. Keywords: Islamic Religious Education; Learning Strategies; Religious Character; Non-Formal Education; Majelis Taklim